Edible Wild Fruit Trees and Shrubs and Their Socioeconomic Significance in Central Ethiopia - Seyoum, Yigremachew; Teketay, Demel; Shumi, Girma; Wodafirash, Melaku (Ethnobotany Research and Applications, 2015)
An ethnobotanical study was conducted to investigate indigenous knowledge and socioeconomics of edible wild fruit trees and shrubs (EWFTSs) in Arsi Zone, Central Ethiopia. A total of 90 respondents were interviewed and consisted of men, women, and children who were selected by stratified random sampling. A total of 30 EWFTSs bearing species that belong to 20 families were identified. Age and gender distribution of respondents on the choice of four of the top five species were homogeneous indicating that promotion can be planned indifferently to all households. Indigenous knowledge on EWFTSs varied significantly (P < 0.05) with age groups and gender as well as area of respondents. Elder males appeared more familiar with EWFTSs. Income generated from sales of EWFTSs is, however, marginal. A considerable proportion of the community acknowledged food values of EWFTSs, and more than half preferred EWFTSs over cultivated commercial fruit, suggesting that efforts towards their integration into the current farming system are appealing. Realizing the resource depletion, about 54% of the respondents planted EWFTSs while 87% showed interest to participate in domestication programs. The study explored a great potential of promoting EWFTSs in Arsi Zone and assisting the country’s efforts of ensuring food security. <!–[endif] –>